2014
DOI: 10.1016/j.ejop.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Free-living amoebae (FLA) co-occurring with legionellae in industrial waters

Abstract: Legionella pneumophila is known as the causative agent of Legionnaires’ disease and free-living amoebae (FLA) can serve as vehicles for legionellae. The aim of this study was to screen industrial waters for the occurrence of FLA and their co-occurrence with legionellae. A total of 201 water samples, including 129 cooling waters and 72 process waters, and 30 cooling lubricants were included in the study. Treated waters were screened periodically, pre and post treatment. Altogether, 72.6% of the water samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
2
44
0
2
Order By: Relevance
“…In each soil, a predominant genus was identified: Tetramitus in Burkina Faso and V1, Naegleria in V2, and Acanthamoeba in France. Previous studies showed that Acanthamoeba and Vermamoeba are the most represented genus of FLA in the environment and more particularly in industrial waters (Scheikl et al 2014), hospital water networks (Thomas et al 2006;Muchesa et al 2017), drinking water (Delafont et al 2013), cooling towers (Atlan et al 2012;Scheikl et al 2016), and soils from the Negev Desert (Rodriguez Zaragoza et al 2005). Our results on the French soil are in accordance to these previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In each soil, a predominant genus was identified: Tetramitus in Burkina Faso and V1, Naegleria in V2, and Acanthamoeba in France. Previous studies showed that Acanthamoeba and Vermamoeba are the most represented genus of FLA in the environment and more particularly in industrial waters (Scheikl et al 2014), hospital water networks (Thomas et al 2006;Muchesa et al 2017), drinking water (Delafont et al 2013), cooling towers (Atlan et al 2012;Scheikl et al 2016), and soils from the Negev Desert (Rodriguez Zaragoza et al 2005). Our results on the French soil are in accordance to these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…These bacteria were named ARB for Bamoebaeresistant bacteria^ (Greub and Raoult 2004) or bacterial endocytobionts (Scheid 2014;Balczun and Scheid 2017). Among them, there are obligate or facultative intracellular bacteria such as Chlamydia-related bacteria (Schmitz-Esser et al 2008), but also various species known as human pathogens such as Legionella pneumophila, Streptococcus pneumoniae, Bacillus cereus, Staphylococcus aureus, or Mycobacterium avium (Cirillo et al 1997;Huws et al 2008;Evstigneeva et al 2009;Scheikl et al 2014). It was recently shown that the bacterial community associated with FLA present in drinking water networks was dominated by Proteobacteria, namely Pseudomonas and Stenotrophomonas genera (Delafont et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability of W. magna C2c Maky to decrease the number of internalized L. pneumophila is confirmed. These results support the idea that W. magna C2c Maky possesses unique behaviour in regard to L. pneumophila strains.Pathogens 2020, 9, 105 2 of 15 Free-living amoebae (FLA) are ubiquitous protozoa that inhabit common aquatic environments and are frequently co-isolated with L. pneumophila in water cooling towers [11,12]. FLA are predatory and consume bacteria to facilitate their growth [13,14]; however, some bacteria such as L. pneumophila have evolved to avoid the phagolysosome fusion and can multiply within FLA, ultimately killing these amoebae before disseminating into the environment [9,[15][16][17].…”
mentioning
confidence: 99%
“…Foram identificadas as amebas de vida livre potencialmente patogênicas Naegleria fowleri e Acanthamoeba spp. em poeira de ambiente hospitalar no Brasil (21,22), e em águas com esgoto industrial na Áustria (23). Em um estudo realizado na Espanha durante um ano em 223 amostras de água, utilizando RT-PCR e cultura, foi identificada a presença de Acanthamoeba spp.…”
Section: Resultsunclassified